1956
DOI: 10.1007/bf02612292
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the nutritive value of thermally oxidized oils

Abstract: Summary Thermal oxidation of corn oil under laboratory conditions, at 200°C., led to the formation of an oil exhibiting definite growth‐depressing action under bothad libitum and paired feeding conditions. Under similar conditions margarine base stock gave only slight growth depression, and none was noted with butter oil. The effect was not a permanent one as animals that were changed to a normal diet quickly recovered and grew to maturity. It appeared that the products formed during the thermal treatment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1958
1958
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…I n addition, there is some evidence of toxicity when oxidized and polymerized oils are given at high levels, oils containing major proportions of polyunsaturated fatty acids being more liable to develop objectionable changes of this type on heating or on storage than edible oils and fats of lower unsaturation. Johnson, Sakuragi & Kummerow (1956) found that the growth-depressing action of thermally oxidized edible oils was related to the decrease in iodine value: maize oil oxidized at 200' until its iodine value had decreased by 16 or 18 units causing severe growth depression, diarrhoea and deterioration in appearance when given to rats at the 20% level in a synthetic diet.…”
Section: Vol Imentioning
confidence: 99%
“…I n addition, there is some evidence of toxicity when oxidized and polymerized oils are given at high levels, oils containing major proportions of polyunsaturated fatty acids being more liable to develop objectionable changes of this type on heating or on storage than edible oils and fats of lower unsaturation. Johnson, Sakuragi & Kummerow (1956) found that the growth-depressing action of thermally oxidized edible oils was related to the decrease in iodine value: maize oil oxidized at 200' until its iodine value had decreased by 16 or 18 units causing severe growth depression, diarrhoea and deterioration in appearance when given to rats at the 20% level in a synthetic diet.…”
Section: Vol Imentioning
confidence: 99%
“…The current generation is being socialized to enjoy the fast-food hamburger as well as many deep-fat fried foods such as fried chicken, fish pieces, french fries, and a variety of chips (Smith et al, 1985). Investigators studying fat derived from commercial deep-fat frying operations have demonstrated either substantial adverse reactions (Johnson et al, 1957;Poling et al, 1962;Sugai et al, 1962;Yoshida et al, 1975;Meltzer et al, 1981) or moderate nutritional effects (Keane et al, 1959;Nolen et al, 1967;Poling et al, 1970;Nolen, 1973) from feeding animals diets containing fats subjected to the heat and oxidation of normal usage. The commercially used fats normally were considered to be no longer fit for human consumption, or had reached the end of their frying life.…”
Section: Introductionmentioning
confidence: 99%
“…There is sorne evidence in the early 1iterature that butterfat may have nutritional advantages over vegetable oils as... a cooking fat (Johnson et...al., 1956; Bhale ['ao et aL, 1959;Coombs et aL, 1965 A typical composItIon of the lipids in whole bovlne'mllk 1s given in Table 1. (Kurtz, 1974).…”
mentioning
confidence: 99%